“NETs and EETs, a Whole Web of Mess” - Tyler L. Williams; Balázs Rada; Eshaan Tandon; Monica C. Gestal (Microorganisms, 2020)
Neutrophils and eosinophils are granulocytes that have very distinct functions. Neutrophils are first responders to external threats, and they use different mechanisms to control pathogens. Phagocytosis, reactive oxygen species, and neutrophil extracellular traps (NETs) are some of the mechanisms that neutrophils utilize to fight pathogens. Although there is some controversy as to whether NETs are in fact beneficial or detrimental to the host, it mainly depends on the biological context. NETs can contribute to disease pathogenesis in certain types of diseases, while they are also undeniably critical components of the innate immune response. On the contrary, the role of eosinophils during host immune responses remains to be better elucidated. Eosinophils play an important role during helminthic infections and allergic responses. Eosinophils can function as effector cells in viral respiratory infections, gut bacterial infections, and as modulators of immune responses by driving the balance between Th1 and Th2 responses. In particular, eosinophils have biological activities that appear to be quite similar to those of neutrophils. Both possess bactericidal activity, can activate proinflammatory responses, can modulate adaptive immune responses, can form extracellular traps, and can be beneficial or detrimental to the host according to the underlying pathology. In this review we compare these two cell types with a focus on highlighting their numerous similarities related to extracellular traps.